Yttrium-90 Radioembolization for Metastatic Colorectal Cancer: Outcomes by Number of Lines of Therapy - Marsala, Andrew; Lee, Edward W.; Padia, Siddharth A. (Seminars in Interventional Radiology, 2017)
Metastatic colorectal cancer represents the most common liver malignancy, and imparts a very poor prognosis for those who develop this disease. Unlike primary liver tumors such as hepatocellular carcinoma, which largely develops in patients with underlying cirrhosis, most metastatic liver tumor patients have normal underlying liver function. Owing to this, most will succumb to tumoral replacement of the liver rather than from underlying liver dysfunction. Radioembolization represents a treatment modality that can be used in multiple fashions to treat one or both lobes of the liver. Techniques depend on whether the procedure is used as first-line, second/third-line, or as salvage therapy. Outcomes and complications of radioembolization are presented in this article, as well as background information on colorectal cancer and systemic therapies.
Keywords: colorectal cancer; interventional radiology; radioembolization; chemotherapy; transarterial therapy